Effectiveness of Topical Tazarotene 0.1% Gel Versus Oral Fluconazole in Treatment of Onychomycosis - Khan, Muhammad Ammar; Anjum, Muhammad; hassan, Laila; niazi, Saira; Naveed, Safoora; Afzal , Umaima (Pakistan Armed Forces Medical Journal, 2025)
Objective: The objective of this study was to assess the comparative effectiveness of topical Tazarotene 0.1% gel and weekly oral Fluconazole in the treatment of onychomycosis. Study Design: Comparative prospective study. Place and Duration of Study: Pak-Emirates Military Hospital, Rawalpindi, Pakistan, from July 2023 to Dec 2023. Methodology: A total of 114 patients fulfilling the inclusion criteria were included in the research. A detailed history, dermatological examination, dermoscopy, and calculation of the Onychomycosis Severity Index (OSI) were employed in each patient to record the severity of their disease. The patients were randomized into two groups, i.e., Group-A, where twice daily application of topical Tazarotene 0.1% gel was applied for three months, and Group-B, where weekly oral Fluconazole tablet of 150mg was administered for three months. The Potassium Hydroxide mounts from nail material was performed at the end of treatment period in all the patients. Results: Of the total, 53(46.5%) were male and 61(53.5%) were female. Following the comparison between two groups, a statistically significant difference was observed, suggesting that treatment with weekly oral Fluconazole (Group-B) had higher effectiveness and better treatment success compared to topical Tazarotene 0.1% gel (Group-A) in terms of the fall in the degree of OSI, dermoscopic findings, clinical evaluation, and potassium hydroxide (KOH) mount after treatment. Conclusions: The effectiveness of Oral weekly Fluconazole is significantly higher than topical Tazarotene 0.1% gel in onychomycosis.